2013
DOI: 10.4067/s0717-97072013000400074
|View full text |Cite
|
Sign up to set email alerts
|

Study Based on Electronic Descriptors of the Diastereoselective Aza-Diels-Alder Cycloaddition of [(1r)-10-(N,n-Diethylsulfamoyl)isobornyl] 2h-Azirine-3-Carboxylate to E,e-1,4-Diacetoxy-1,3-Butadiene

Abstract: Cycloaddition of chiral [(1R)-10-(N,N-diethylsulfamoyl)isobornyl] 2H-azirine-3-carboxylate to E,E-1,4-diacetoxy-1,3-butadiene shows complete diatereoselectivity giving a single cycloadduct (-)Our main objective is to identify electronic/steric parameters capable of describing the observed tendencies of this reaction. The results of the calculations conclude that: even though the steric factors can play an important role at the initial steps of the reaction, at the transition states the behavior of several elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Previous studies have systematically reported the exo cycloadducts to be sterically less hindered, and thus thermodynamically more stable than their endo counterparts. 6,9,10,17,41 In this study, however, we noticed the endo products with R 1 ¼ tBu to be slightly more stable than their exo analogues when considering their energy at 0 K relative to the free reactants, DE Prod . These results are depicted in Fig.…”
Section: Final Productsmentioning
confidence: 55%
See 1 more Smart Citation
“…Previous studies have systematically reported the exo cycloadducts to be sterically less hindered, and thus thermodynamically more stable than their endo counterparts. 6,9,10,17,41 In this study, however, we noticed the endo products with R 1 ¼ tBu to be slightly more stable than their exo analogues when considering their energy at 0 K relative to the free reactants, DE Prod . These results are depicted in Fig.…”
Section: Final Productsmentioning
confidence: 55%
“…6,9,10,17,41 In this study, however, we noticed the endo products with R 1 ¼ tBu to be slightly more stable than their exo analogues when considering their energy at 0 K relative to the free reactants, DE Prod . These results are depicted in Fig.…”
Section: Final Productsmentioning
confidence: 82%